Critical data‐based re‐evaluation of minocycline as a putative specific microglia inhibitor. Issue 10 (1st June 2016) - Möller, Thomas; Bard, Frédérique; Bhattacharya, Anindya; Biber, Knut; Campbell, Brian; Dale, Elena; Eder, Claudia; Gan, Li; Garden, Gwenn A.; Hughes, Zoë A.; Pearse, Damien D.; Staal, Roland G. W.; et al.
Abstract : Minocycline, a second generation broad‐spectrum antibiotic, has been frequently postulated to be a "microglia inhibitor." A considerable number of publications have used minocycline as a tool and concluded, after achieving a pharmacological effect, that the effect must be due to "inhibition" of microglia. It is, however, unclear how this "inhibition" is achieved at the molecular and cellular levels. Here, we weigh the evidence whether minocycline is indeed a bona fide microglia inhibitor and discuss how data generated with minocycline should be interpreted. GLIA 2016;64:1788–1794 Main Points: Minocycline is not a specific microglia inhibitor. Minocycline has bona fide effects on neuroinflammation in vivo. Data generated with minocycline are difficult to interpret.